THE CHALLENGES OF ESP TEACHING AND HOW THE USE OF ICT CAN HELP TO ADDRESS THEM: A SOCIAL-SEMIOTIC PERSPECTIVE - Latifa Ika Sari; Abdurrachman Faridi; Dwi Rukmini; Januarius Mujiyanto (Universitas Muhammadiyah Semarang, 2021)
The advancement of technology has brought remarkable changes in language education. The integration of Information and communications technology (ICT) into language classrooms is unavoidable. This research attempts to investigate the challenges of ESP teaching and explore how the use of ICT can help to address them. The social-semiotic perspective is used due to its relevance with ESP teaching. The authors employed a case study conducted in the Port and Shipping Management Department at a Maritime Polytechnic in Semarang, Indonesia. Data were collected by conducting an interview with an English teacher and having Focus Group Discussions (FGD) with a group of students. The result of this study indicates that teachers’ limited knowledge of social practices in the Port and Shipping Industry causes obstacles in selecting relevant teaching materials and activities. To address the challenges, teachers can use various sources, such as websites and video-sharing platforms which are rich with samples of authentic communication. To deal with authentic materials which have a high level of difficulty, teachers need strategies such as scaffolding and giving consistent feedback to students’ performance.